Simultaneous pancreas and kidney transplantation: Incidence and risk factors for amputation after 10‐year follow‐up. Issue 6 (19th April 2017) - MacCraith, Eoin; Davis, Niall F.; Browne, Cliodhna; Mohan, Ponnusamy; Hickey, David
Abstract: Introduction: The incidence of amputation after simultaneous pancreas and kidney (SPK) transplantation ranges from 9.5% to 23% after 5 years of follow‐up. The objective of this study was to investigate the incidence and risk factors for amputation in SPK transplant patients compared to kidney transplantation alone (KTA) after a minimum follow‐up of 10 years. Methods: An analysis was performed on a prospectively maintained database of 81 SPK transplants and 43 KTA consecutively performed in one center for insulin‐dependent diabetes mellitus between December 1992 and January 2006. Primary outcome variables were incidence of amputation per patient, total number of amputations, and type of amputation performed. Data are presented as a mean ± standard deviation. Results: Seven patients (9%) in the SPK cohort and one patient (2%) in the KTA cohort underwent amputation ( P <.001). One amputee had pancreas allograft failure prior to amputation. Fifteen amputations were performed in total and four patients required ≥2 amputations. The latency period between transplantation and amputation was 133.57±49.43 months in the SPK cohort and 168 months in the KTA group. Conclusions: The incidence of amputation after SPK transplantation is approximately 9% after 10‐year follow‐up. Patients are at a significantly greater risk of amputation after SPK transplantation compared to KTA for type 1 diabetes despite insulin independence.